Securing Data Communication for Data Driven Applications Using End to End Encryption - Subhi Almohtasib; Alaa H Al-Hamami (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Many users of smartphones have secret data they want to save it on their devices. The probability of a device damage or stolen prevents them from saving data. Therefore, data driven applications used to save user’s data on a remote server. Protection of the data during its transmission considered as one of the success aspect for these applications. In this paper, an enhanced method for data encryption proposed which guarantees data secrecy during its transmission over network. User’s data encrypted before transmission using Base64 class. Data encryption and decryption implemented to halt reverse encryption process. In this way, data is transmitting in a secure and efficient manner accomplishing the main goal of Cryptography.